The Diagnostics of Professional Focus and Value-Oriented Sphere of Personality in the System of Higher Education - Lilia Romankova (Vasyl Stefanyk Precarpathian National University, 2017)
This article examines the importance of psychological and pedagogical research in the field of professional focus and value orientation sphere of personality in the higher education system, which can provide an opportunity to model the pedagogical activity in order to shape important professional qualities of future specialists.